Entrepreneurial Education Strengthening Resilience, Societal Change and Sustainability - Seikkula-Leino, Jaana; Westerberg, Mats; Verma, Priti; Salomaa, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Working life is in a major transition and environmental, societal, and economic problems challenge human activities. The need to develop reliance and sustainability also through higher education is evident. It has been anticipated that emphasis on entrepreneurship competencies will be even stronger in the future. In this reprint, we provide insights on how to develop entrepreneurial competencies within higher education and its existing networks. It guides the reader to understand how political documents steer the implementation of global goals and what could be improved. Second, we present how pedagogical solutions and models can meaningfully support the development of entrepreneurial competencies in the field of higher education. We show the complexity of this phenomenon, thus developing a deeper understanding of this educational issue. Third, we highlight the essence of developing teacher education in this context. Fourth, we stress that entrepreneurial competencies are also needed in the working life. We present some interesting key points for developing entrepreneurial higher education from the entrepreneurial ecosystem point of view. It consists of 13 articles from international scientific experts in this field and provides new knowledge, ideas and opportunities for creating practices to enhance the development entrepreneurial, sustainable and resilient societies. It is targeted to researchers, policy-makers, higher education providers, stakeholders, educators and trainers.